GAMBARAN SELF REGULATED LEARNING SISWA TERHADAP PEMBELAJARAN DARING PADA MASA PANDEMI COVID 19 - Novia Khoerunnisa; Euis Eti Rohaeti; Devy Sekar ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This study aims to determine the description of students who have self-regulated learning towards online learning during the COVID-19 pandemic at SMPN 2 Pakisjaya, Karawang Regency. This research is based on phenomena that occur in schools. There are some students who have low self-regulated learning in online learning. The method used in this study is a qualitative method with a descriptive type of research. Data collection techniques used in this research is to use observation, interviews. The subjects in this study were 3 students who had low self-regulated learning towards online learning during the covid-19 period. The results of this study found that students during the online learning process experienced difficulties in self-regulation in learning, this was seen from the aspects of metacognition, motivation and behavior. The factors that influence students' self-regulated learning are internal factors and external factors. Keywords: : Self regulated learning, Online learning, Covid-19